Ischemic Stroke of Brain 2018
DOI: 10.5772/intechopen.76918
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vein and Dural Sinus Thrombosis

Abstract: Cerebral venous thrombosis (CVT) is an uncommon disorder in the general population. At least 1 risk factor can be identified in 85% of patients with CVT. Because of the high frequency of thrombophilia among patients with CVT, screening for hypercoagulable conditions should be performed. Two pathophysiological mechanisms contribute to their highly variable clinical presentation. Four major syndromes have been described: isolated intracranial hypertension, focal neurological abnormalities, seizures, and encephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…According to Southwick et al (1986), in addition to the clinical signs mentioned above, there can be a large spectrum of other symptoms like cranial nerve palsies, diplopia, even decreased visual acuity, seizures or focal neurological signs like motor deficits, which make the diagnosis of CST challenging [1]. Seizures and motor dysfunction can occur if the occlusion spreads to other sinuses and cortical veins [8].…”
Section:  Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Southwick et al (1986), in addition to the clinical signs mentioned above, there can be a large spectrum of other symptoms like cranial nerve palsies, diplopia, even decreased visual acuity, seizures or focal neurological signs like motor deficits, which make the diagnosis of CST challenging [1]. Seizures and motor dysfunction can occur if the occlusion spreads to other sinuses and cortical veins [8].…”
Section:  Discussionmentioning
confidence: 99%
“…As it was mentioned before in many studies, CST usually has an infectious cause. It represents the single cerebral veins and dural sinuses thrombosis which results in a distinct clinical condition that involves: chemosis, conjunctival edema, proptosis and painful ophthalmoplegia [ 8 , 9 , 10 , 11 , 12 ]. Frequently, the symptoms start with the involvement of an eye, however, within a few days the other eye tends to be affected via intracavernous sinuses.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Nicolini and colleagues reported that fetuses born with porencephaly had a higher hematocrit level than other normal fetuses [8]. It has been noted that local causes including porencephaly can determine dural sinus and cerebral sinus occlusions [9]. However, the occurrence of both hemorrhage and thrombosis in the same patient with porencephaly has not been clearly reported in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of cerebral sinus thrombosis is based on neuroimaging. A CT scan should be included in the diagnostic strategy for ruling out other acute cerebral disorders that sinus thrombosis can imitate including arterial stroke, abscess, tumors and subarachnoid hemorrhage [9]. CT venography is especially useful in the acute setting because it provides a rapid and reliable method for detection of sinus thrombosis, particularly in patients with contraindications to MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation